Effect of herbal powder, Ferula asafoetida, on the conception rate of rats - Kanhye, Umika (2016)
Rats are reservoirs for Leptospirosis and many vector borne diseases. According to the Malaysian Pest Control Association, the rat population in Kuala Lumpur, in 2010, was 4.4 million and 2013, 6.8 million. Despite massive trapping, the population did not decrease significantly and the main reason being the rapid rat breeding capacity. One of the ways to control breeding is to use a local herb, Ferula asafoetida, which has contraceptive properties. This study aimed to observe the effect of asafoetida powder on the conception rate of rats. One male and six female Sprague dawley rats were used for this study. Three female were given 400 mg of asafoetida powder mixed in water daily as a treatment group, while the other three from the control group were given fresh water. The male was introduced to the female cage for one week mating. Results showed that animals in control group increased their body weight, had distended abdomen and hair loss around the teats. However, for the treatment group there was no pregnancy sign observed; leading to two possible factors,masking of female pheromone or failure of implantation. Thus, this could indicate that asafoetida powder is a natural, safe herb to control rat population and the spread of diseases.